2020
DOI: 10.1002/suco.202000135
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of interfacial transition zone of sustainable concrete with recycled and steel slag as aggregate

Abstract: Utilizing steel slag and recycled concrete as fine aggregate could save the consumption of natural resource and reduce the environmental pollution. In this work, the effect of steel slag aggregate and recycled aggregate on the compressive strength and chloride migration coefficient of three types of concretes were investigated and compared with natural aggregate. The interfacial transition zone (ITZ) microstructure and the connection between aggregate and bulk cement matrix was determined by using a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…However, it should be noted that the destruction of concrete structures subject to static and dynamic effects is determined by the quality of ITZ in the area of coarse aggregate grains [45][46][47][48][49][50]. It was proved in paper [50] that W c in this zone is lower by almost 35% in the case of concretes modified with 20% FA additive.…”
Section: Introductionmentioning
confidence: 95%
“…However, it should be noted that the destruction of concrete structures subject to static and dynamic effects is determined by the quality of ITZ in the area of coarse aggregate grains [45][46][47][48][49][50]. It was proved in paper [50] that W c in this zone is lower by almost 35% in the case of concretes modified with 20% FA additive.…”
Section: Introductionmentioning
confidence: 95%
“…As SSA is stronger than NA and has a rougher surface than NA, the bonding strength with the cement slurry increases. However, the addition of SSA increases the porosity of the concrete, and owing to its high angularity, steel slag requires more cement to cover its surface, which reduces the strength of the concrete [92]. These positive and negative effects have a competitive effect, resulting in an overall increase or decrease in strength.…”
Section: Influence Of Slag On Compressive Strength Of Concretementioning
confidence: 99%
“…On the other hand, the consumption of concrete in engineering construction is huge, but the natural aggregate is increasingly exhausted, which makes the search for the substitute of natural aggregates to make concrete become a research hotspot. Some scholars intended to use the steel slag as aggregates to prepare steel slag concrete (SSC), and have obtained some achievements 5–9 . Hisham 10 used the steel slag as fine aggregates and found that when the replacement ratio was between 15% and 30%, the enhancement of compressive strength was best.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars intended to use the steel slag as aggregates to prepare steel slag concrete (SSC), and have obtained some achievements. [5][6][7][8][9] Hisham 10 used the steel slag as fine aggregates and found that when the replacement ratio was between 15% and 30%, the enhancement of compressive strength was best. Shekhar 11 indicated that as coarse aggregates, when the replacement ratio of steel slag was below 50%, the concrete strength increased with the rise of the replacement ratio.…”
Section: Introductionmentioning
confidence: 99%